PENGARUH TUNJANGAN KINERJA DAERAH (TKD) TERHADAP PELAYANAN PUBLIK ( Suatu Studi Pada Dinas Kesehatan Kota Ternate Provinsi Maluku Utara ) - Ramli, Hariyati; Kiyai, Burhanuddin; Ruru, Joorie Marhaen (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: This study aimed to "analyze the influence of regional performance benefits to public serviceIn the City Health Office Ternate North Maluku province" to explain Effect Benefit performance ofRegional Against Public Service is the allowance given to servants which is a function of thesuccessful implementation of bureaucratic reforms and based the gains of the Civil Servants in linewith the achievement of the organization's performance in which the Servant of the work. Therefore,the individual performance benefits Servants may increase or decrease in line with the increase ordecrease in performance measured by Key Performance Indicators lnstansi.Based on the characteristics of the issues raised in this study, the approach used by theapplication of the relevant quantitative descriptive method (Nazir 1988; Koentjaraningrat, 1997); andekplanatoris survey (Vredenbreght, 1981: 41). This is possible because in addition to this study want touncover problems that are actual and factual, it also aims to find circuit / influence of one factor orsymptoms by a factor or other symptoms. According Vredenbreght (1981: 41), that the explanatorysurvey method is a method used to test a hypothesis or, more generally, to explain the relationshipsbetween variables.Presidential Regulation No. 81 Year 2010 concerning the Grand Design Reforms 2010-2025mandates entire Ministries / Agencies and Local Government to conduct bureaucratic reform.Ministries / Agencies and Local Government has awarded bureaucratic reform in the form ofperformance benefits.Results of the assessment of the program and activities of the bureaucratic reform Ministry /Agency which conducted the National Bureaucracy Reform Team (TRBN) used by the Ministry ofFinance for consideration in the calculation of the amount of allowances of performance and are usedin the process of determination of the amount approved in the Meeting KPRBN performance benefits.Furthermore, the amount of allowances of performance after approval OPR determined byPresidential Decree. Referring to the respondents' assessment of the two elements of the quality ofpublic services at the City Health Office of Ternate, was not much different, but when observed moreevidently ratings higher than the employee element of the community assessment service users.Keywords: Effect of Local Perf